ANALISIS KUALITAS LAPORAN KEUANGAN PADA KOMISI PEMILIHAN UMUM - Padang, Novi Natalia (Jurnal Riset Akuntansi & Keuangan, 2024)
The aim of this research is to determine and analyze the accountability of the General Election Commission in preparing financial reports using a qualitative approach. This research emphasizes the concept of accountability and finds weaknesses in the implementation of financial management. The subject of this research is the General Election Commission. The KPU has received an Unqualified Audit Opinion (WTP) from BPK RI. This research was carried out to analyze using scientific research